Rule of Civil Procedure UK 1998 (Journal of actual problems of jurisprudence, 2018)
This article discusses the features of the legal system of one of the most developed countries of the United Kingdom in Europe. In the UK, a form of litigation is a civil procedure. The main source of Civil Procedure, which entered into force on 26 April 1999 is a rule of civil procedure. In this article there is an attempt to answer the above questions. The article discusses that the comprehensive study rules of the problems from the standpoint of logic, psychological and legal unity achieved the best result. The article sums up the results of the study on the legally relevant circumstances.Key words: system, rule, law, court.